2015
DOI: 10.3390/molecules200610800
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Studies on Rutaecarpine. II.—Synthesis and Structure-Biological Activity Relationships

Abstract: Rutaecarpine is a pentacyclic indolopyridoquinazolinone alkaloid found in Evodia rutaecarpa and other related herbs. It has a variety of intriguing biological properties, which continue to attract the academic and industrial interest. Studies on rutaecarpine have included isolation from new natural sources, development of new synthetic methods for its total synthesis, the discovery of new biological activities, metabolism, toxicology, and establishment of analytical methods for determining rutaecarpine content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 71 publications
1
33
0
Order By: Relevance
“…They are present in several plant families as secondary metabolites, including the Strychnaceae, Apocynaceae, Rutaceae, and Rubiaceae [10]. Rutaecarpine is an indolopyridoquinazolinone alkaloid with diverse biological activities which is one of the main components isolated from the unripe fruits of the traditional Chinese medicine Tetradium ruticarpum (A. Jussieu) T. G. Hartley (synonym: Euodia ruticarpa) ( Figure 1) [12][13][14][15]. The beneficial properties of rutaecarpine have led to a high demand for extracts containing rutaecarpine in the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%
“…They are present in several plant families as secondary metabolites, including the Strychnaceae, Apocynaceae, Rutaceae, and Rubiaceae [10]. Rutaecarpine is an indolopyridoquinazolinone alkaloid with diverse biological activities which is one of the main components isolated from the unripe fruits of the traditional Chinese medicine Tetradium ruticarpum (A. Jussieu) T. G. Hartley (synonym: Euodia ruticarpa) ( Figure 1) [12][13][14][15]. The beneficial properties of rutaecarpine have led to a high demand for extracts containing rutaecarpine in the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that Ru has many biological activities, such as anti-inflammatory, anti-obesity, anti-hypertensive, and it is used for the treatment of cardiovascular diseases [ 24 , 25 , 26 , 27 , 28 ]. The anti-tumor activity of Ru is weak, and its underlying mechanism is unclear [ 29 ]. However, the anti-angiogenic effects of Ru have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Rutaevin, evodiamine, and rutaecarpine were determined quantitatively in the EEER used in this study ( Figure 1 and Figure 2 ). Rutaecarpine exhibits pharmacological properties, including a cardiovascular effect, antiplatelet activity, and anti-inflammatory activity [ 34 ]. Evodiamine has a robust anticancer bioactivity via the inhibition of cell proliferation or the induction of apoptosis [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%